Study guides

☆☆

Q: What does '2a 2b 3a 3b a b' equal?

Write your answer...

Submit

Still have questions?

Related questions

6a2 + 5ab - 6b2 = 6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)*(3a - 2b)

2a

(3a - 2b)(2a + 3b)

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

-2a plus 3b

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).

6 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -3

6a2 + 5ab - 6b2 = (3a - 2b)(2a + 3b)

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

Gathering like terms together, this is equal to 5a + 3b + 7c.

1a+3b 2a+4b=3a +7b

3a - 2b

2,3,2a,3a,3b,2b,3b^2,2b^2

Considering the minus sign between 5ab and 6b2 then we have the polynomial as 6a2 + 5ab - 6b2. The polynomial is a quadratic polynomial.Steps to factorize a quadratic polynomial:1 - Multiply first term by third term. 6a2 x (-6b2) = -36a2b22 - If possible break the second term into two terms such that they multiple to -36a2b2. If not then it is factorized by Sridharacharya's formula.5ab can be broken as 9ab + (-4ab).These two terms multiply to give -36a2b2.So we can write 6a2 + 5ab - 6b2 = 6a2 + 9ab + (-4ab) - 6b2.6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)(3a - 2b).So the factors are (2a + 3b) and (3a - 2b).

2a x 3b = 6ab

2a

6a²b - 12ab²

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals". There are no operator symbols before 3a and 3b.

3a - 2b

-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b

2a x 3b = 6ab

No. 2a is one thing, 3b is another. If you add them together, they become 2a + 3b. 5ab indicates that multiplication has taken place. 5 times a times b = 5ab

2A plus 3B times 2A - 3B = 4A2 - 9B2; this is an example of the general formula (a + b)(a - b) = a2 - b2.

ab + 2a + 3b + 6

The given expression can be simplified to: 3b-a

People also asked